1997
DOI: 10.1021/ma9618585
|View full text |Cite
|
Sign up to set email alerts
|

Static Properties of Homopolymer Melts in Confined Geometries Determined by Monte Carlo Simulation

Abstract: The static properties of a homopolymer melt between energetically neutral walls are studied as a function of the degree of confinement (plate spacing) and polymer molecular weight. The cooperative motion lattice model is used and allows all calculations to be performed at full occupancy (i.e., at a volume fraction of 1); chain lengths varying from 384 to 24 are examined. Properties investigated include the magnitude of the end-to-end vector, the radius of gyration, and components of the end-to-end vector. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 17 publications
(36 reference statements)
6
26
0
Order By: Relevance
“…Unentangled polymer melts with N w = 64 and [30,31,35]. Results for the unentangled case closely parallel the results for the entangled case; one distinction is that for entangled chains wall slip provides a slight shear rate gradient near the wall which is absent in the unentangled case (see velocity profiles).…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Unentangled polymer melts with N w = 64 and [30,31,35]. Results for the unentangled case closely parallel the results for the entangled case; one distinction is that for entangled chains wall slip provides a slight shear rate gradient near the wall which is absent in the unentangled case (see velocity profiles).…”
Section: Resultssupporting
confidence: 60%
“…For the model applied to monodisperse linear chains it is found that the equilibrium ensemble averaged root mean squared end-to-end vector [32], R 2 1/2 , scales as: [35] …”
Section: Length Scale Matching-the End-to-end Vectormentioning
confidence: 99%
“…Further details of the algorithm are found in earlier works by Gauger et al, 23 Pakula, 24 and Pai-Panandiker and Dorgan. 25 The walls, located at xϭ0 and xϭL x , are impenetrable, neutrally energetic, purely reflective boundaries; periodic boundary conditions are imposed in the y and z-directions. Chain lengths and box dimensions are chosen in order to satisfy the condition of full occupancy.…”
Section: A Simulation Methodsmentioning
confidence: 99%
“…al. 20 examined orientational effects of the end-to-end vector in a Monte-Carlo Simulation of dense polymer films. They found an increasing alignment of the end-to-end vector with reducing L z , but averaged their quantities over the whole film.…”
Section: Discussionmentioning
confidence: 99%